Pengembangan Media Pembelajaran Digital Berbasis Aplikasi Zep Quiz untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas V Sekolah Dasar - Nurlita Lestari; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to describe the results of a literature review on the use of digital learning media based on the Zep Quiz application in the learning process in elementary schools. This study was conducted to determine the feasibility, effectiveness, and attractiveness of Zep Quiz as an innovative and enjoyable digital learning medium. The method used was a Systematic Literature Review (SLR) by searching articles from Google Scholar using the keyword